Cultural membership and civicness : cultural self-awareness, identification, and civic motivation - Lim, Queenie Wan Rui (Nanyang Technological University, 2021)
Civic participation involves individuals’ positive engagement with one’s society. Strong collective identification drives participation in actions beneficial for the collective. Self-oriented civic motivation facilitates civic participation as participation aligns with individuals’ personal values, whereas other-oriented civic motivation facilitates civic participation via concern for society. Cultural self-awareness involves the increased awareness of one’s culture influencing the self. This research explored how cultural self-awareness might influence the effects of collective identification and civic motivation on civic participation, since cultural self-awareness may increase the cognizance of one’s identifications and motivations. We predicted that collective identification and self-oriented civic motivation would both positively predict civic participation, and the relationships would be stronger for individuals with high cultural self-awareness. We also predicted that other-oriented civic motivation would positively predict civic participation, but the relationship would not be influenced by cultural self-awareness. 144 Singaporean young adults completed an online questionnaire at their own convenience, assessing their cultural self-awareness, strength of community and national identification, self-oriented and other-oriented civic motivation, and civic participation both online and offline. Cultural self-awareness did significantly moderated relationships between collective identifications and civic behaviours, and self-oriented civic motivation and civic behaviours. There was a more positive relationship between the variables for individuals with higher cultural self-awareness. As expected, there was no influence of cultural self-awareness on the positive relationship between other-oriented civic motivation and civic behaviour. This suggests that cultural self-awareness is associated with increased awareness of one’s identification and personal motivation, therefore strengthening both identification-behaviour and motivation-behaviour links.